Cell-Free DNA: Hope and Potential Application in Cancer - Yan, Yan-yan; Guo, Qiao-ru; Wang, Feng-hua; Adhikari, Rameshwar; Zhu, Zhuang-yan; Zhang, Hai-yan; Zhou, Wen-min; Yu, Hua; Li, Jing-quan; Zhang, Jian-ye (Frontiers in Cell and Developmental Biology, 2021)
Cell-free DNA (cfDNA) is easily accessible in peripheral blood and can be used as biomarkers for cancer diagnostics, prognostics, and therapeutics. The applications of cfDNA in various areas of cancer management are attracting attention. In this review article, we discuss the potential relevance of using cfDNA analysis in clinical oncology, particularly in cancer screening, early diagnosis, therapeutic evaluation, monitoring disease progression; and determining disease prognosis.